Practical First Aid - Armstrong, Dr. Vivien J.; Authorised By the Britsh RedCross (London Dorling Kindersley, 2003)
From first-aid essentials to life-saving procedures, it's worth having someone who knows what they are doing to cope with life's little (and big) emergencies. This guide provides user-friendly step-by-steps that tell you how to treat more than 100 medical conditions and injuries from minor cuts and burns to choking and poisoning.
Include Index and Colored Illustrations.
Keywords: First Aid in Illness and Injury